2008
DOI: 10.1542/peds.2007-2591
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Using Recombinant Erythropoietin for Neuroprotection in Very Preterm Infants

Abstract: No significant adverse effects of early high-dose recombinant human erythropoietin treatment in very preterm infants were identified. These results enable us to embark on a large multicenter trial with the aim of determining whether early high-dose administration of recombinant human erythropoietin to very preterm infants improves neurodevelopmental outcome at 24 months' and 5 years' corrected age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 50 publications
5
121
0
1
Order By: Relevance
“…The mechanisms behind the reduced incidence of NEC and sepsis are not fully understood; however, rhEPO protects epithelial barrier function and protects intestine from excessive autophagy and apoptosis, and this, as well as rhEPO's immunomodulation actions, might provide beneficial effects in preventing NEC and sepsis 49, 50. Furthermore, there were no adverse effects such as thrombosis, hypertension, polycythemia, or polyplastocytosis observed, which is in line with previous reports,20, 37 suggesting that the current protocol of repeated low‐dose rhEPO treatment in this study is protective and safe.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The mechanisms behind the reduced incidence of NEC and sepsis are not fully understood; however, rhEPO protects epithelial barrier function and protects intestine from excessive autophagy and apoptosis, and this, as well as rhEPO's immunomodulation actions, might provide beneficial effects in preventing NEC and sepsis 49, 50. Furthermore, there were no adverse effects such as thrombosis, hypertension, polycythemia, or polyplastocytosis observed, which is in line with previous reports,20, 37 suggesting that the current protocol of repeated low‐dose rhEPO treatment in this study is protective and safe.…”
Section: Discussionsupporting
confidence: 86%
“…The rates for mortality and morbidities, including ICH and NEC, were not significantly changed by early rhEPO treatment 23. Other recent studies showed that early high‐dose rhEPO (2,500–3,000U/kg) administered once in very preterm infants did not increase the incidence or severity of ROP 20, 37. In the current study, low‐dose rhEPO (500U/kg) treatment decreased the risk of NEC and sepsis and did not increase the risk of ROP or BPD.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Very recently, two safety studies have been concluded in very preterm infants and infants with extremely low birth weight. 120,121 In both studies, high-dose EPO was found well tolerated, causing no excess morbidity or mortality. A dose range of 1000 to 3000 IU/kg was found to yield neuroprotective serum levels.…”
Section: Erythropoietin As Neuroprotective/ Neuroregenerative Treatmementioning
confidence: 85%